(untitled) (Research, Society and Development, 2021)
Brazilian biodiversity represents relevant economic importance for traditional peoples and communities in Brazil when transformed into goods and services destined for the market, constituting value chains. These goods and services are called sociobiodiversity products and can be locally sold and (or) offered to the national and international market. The mangabeira tree was recognized in 1992 in Sergipe, Northeastern Brazil, as its symbol tree due to its high incidence. Then, in 2010, the Mangaba Collectors were recognized as a traditionally differentiated group. Therefore, they must be protected accordingly to their forms of social organization, their territories, and natural resources. They are traditional groups from restinga areas that develop mangaba extractivism and other resources from the restinga and mangrove forests for subsistence and cultural reproduction. Currently, the Mangaba Collectors from Sergipe have been organizing themselves in local associations. Their main goals are to generate work and income through the addition of values to local natural products. In this sense, the objective of this study was to apply the tool Radar de Inovação to assess the degree of innovation of the family agribusiness units of the Mangaba Collectors of Sergipe inserted in the value chain of sociobiodiversity products on the coast of Sergipe. We found that the main factor in selecting innovation actions of the associations analyzed was the location. That happened due to market opportunities peculiar to each region and respective conditions of identification and access.